Chemical analysis of fodder climbers found in Sunsari district, Nepal - Mandal, T. N.; Gautam, T. P. (Nepalese Journal of Biosciences, 2014)
Altogether 19 fodder climbers were collected with local information for their quality, feeding season and preference by livestock from Sunsari district, Nepal. Fodder climbers were distributed under 15 angiospermic families. Among them, 6 climber species were analyzed for dry matter, crude protein, ether extract, crude fibre, N-free extract, total ash and mineral contents (K, Ca, and P). Dry matter content ranged from 24.12 to 45.43%. Crude protein content showed slight variation. Ether extract ranged from 2.13- 4.23%, while Crude fiber content ranged between 18.62 and 22.52%. N-free extract showed narrow variation in the content while Total ash content exhibited a wide variation ranging from 5.67 to 11.52%. Among the minerals, Phosphorus showed distinct variation in the content from 0.19 to 0.46%. Fodder quality assessed by local people was compared with the result of chemical composition. On the basis of local information and chemical composition, Hedera nepalensis and Hedyotis scandens were considered as very good fodder climbers.